Konsep berpikir karl marx dalam membantah logika mistika : studi materialisme klasik - nakhai, rayhan farel; mahtarom, tiara sebastika; Rose, Dara Salsabila; Rohimah, Salsabilla Ainun (Maliki Interdisciplinary Journal, 2026)
The concept of mystical logic is understood as a perspective that views mystical, supernatural, and otherworldly elements as key to comprehending reality. Mystical logic often creates illusions that obscure the fundamental basis of social problems and phenomena, thereby exerting a negative impact on critical thinking and societal conceptual frameworks. As an antithesis, Karl Marx offers the concept of classical materialism, which posits that all reality in the world originates from matter. Marx was inspired by Hegel and Feuerbach in articulating his ideas on classical materialism. This literature aims to refute and dismantle mystical elements in the modern era while contributing to the philosophical literature of science. Ultimately, society needs to enhance awareness of the importance of possessing strong critical faculties and rational reasoning to avoid being trapped in the concept of mystical logic. The role of government, such as providing quality educational facilities and educators, is also crucial in shaping a more insightful and competitive society.